Finding my mind - Walker, Dan (London : BBC, 2009)
Is it possible to gain a complete picture of one's own consciousness? Or will the mind always remain an unsolved jigsaw puzzle? In this program, University of Oxford professor Dr. Marcus du Sautoy takes part in fascinating experiments that probe the complexities of the brain and awareness. After an overview of the mirror-recognition test, du Sautoy undergoes an MRI scan that identifies which part of his brain switches off when he succumbs to an anesthetic. Subsequently, he attempts to stay oriented while monitoring a live video image of himself from behind; endures the illusion of inhabiting another person's body; and copes with other procedures designed to unravel his sense of self.
Originally broadcast as an episode of the BBC television program Horizon, 2009.
Camera, Kevin White, Dirk Nel ; film editor, Tony Quinn.
Presenter: Marcus du Sautoy.
dvd format
Keywords: Consciousness; Awareness; Brain; Spinal Cord